Pengaruh Penambahan Karet Alam (Lateks) Pada Campuran Cold Paving Hot Mix Asbuton (Cphma) Dengan Variasi Perendaman - Munandar, Haris; Nurdin, Abd Rahim; Yunus, Ahmad Yauri (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
CPHMA (Cold Paving Hot Mix Asbuton) is a new breakthrough to meet the needs of remote areas where the asphalt mixing plant (AMP) is inadequate and is expected to add value to stability and durability. Natural Rubber (Latex) is a type of natural rubber that has high resistance to cracking and has high adhesion. The purpose of this study was to determine how much influence the addition of natural rubber (latex) had on marshall characteristics in CPHMA mixtures with variations of immersion. This study used natural rubber (latex) additives with levels of 10%, 15% and 20%. 33 samples of test objects were made, 6 normal samples and 27 variations samples. The treatment of the specimens was carried out with variations of immersion for 7, 14 and 21 days. Testing is done with the marshall test tool. The test results showed that Natural Rubber (Latex) as an added ingredient in CPHMA-type Buton asphalt mixture by immersion caused the value of the properties of the mixture to not meet specifications and could not be used.